Gender differences in the association of individual social class and neighbourhood unemployment rate with prevalent type 2 diabetes mellitus: a cross-sectional study from the DIAB-CORE consortium. Issue 6 (21st June 2013) - Müller, Grit; Hartwig, Saskia; Greiser, Karin Halina; Moebus, Susanne; Pundt, Noreen; Schipf, Sabine; Völzke, Henry; Maier, Werner; Meisinger, Christa; Tamayo, Teresa; Rathmann, Wolfgang; Berger, Klaus
Abstract : Objective: To analyse gender differences in the relationship of individual social class, employment status and neighbourhood unemployment rate with present type 2 diabetes mellitus (T2DM). Design: Five cross-sectional studies. Setting: Studies were conducted in five regions of Germany from 1997 to 2006. Participants: The sample consisted of 8871 individuals residing in 226 neighbourhoods from five urban regions. Primary and secondary outcome measures: Prevalent T2DM. Results: We found significant multiplicative interactions between gender and the individual variables–—social class and employment status. Social class was statistically significantly associated with T2DM in men and women, whereby this association was stronger in women (lower vs higher social class: OR 2.68 (95% CIs 1.66 to 4.34)) than men (lower vs higher social class: OR 1.78 (95% CI 1.22 to 2.58)). Significant associations of employment status and T2DM were only found in women (unemployed vs employed: OR 1.73 (95% CI 1.02 to 2.92); retired vs employed: OR 1.77 (95% CI 1.10 to 2.84); others vs employed: OR 1.64 (95% CI 1.01 to 2.67)). Neighbourhood unemployment rate was associated with T2DM in men (high vs low tertile: OR 1.52 (95% CI 1.18 to 1.96)). Between-study and between-neighbourhood variations in T2DM prevalence were more pronounced in women. The considered covariates helped to explain statistically the variation in T2DM prevalence among men, but not among women. Conclusions: Social class was inversely associated with T2DM in both men and women, whereby the association was more pronounced in women. Employment status only affected T2DM in women. Neighbourhood unemployment rate is an important predictor of T2DM in men, but not in women.